Influence of Age, BMI, Gender and Lumbar Level on T1ρ Magnetic Resonance Imaging of Lumbar Discs in Healthy Asymptomatic Adults - Gübitz, Raphael; Lange, Tobias; Gosheger, Georg; Heindel, Walter; Allkemper, Thomas; Stehling, Christoph; Gerss, Joachim; Kanthak, Christian; Schulte, Tobias L. (RöFo - Fortschritte auf dem Gebiet der Röntgenstrahlen und der bildgebenden Verfahren, 2018)
Purpose To assess the T1ρ range of lumbar intervertebral discs in healthy asymptomatic individuals at 1.5 T and to investigate the influence of age, body mass index (BMI), gender, and lumbar level on T1ρ relaxation.Materials and Methods In a prospective study, a total of 81 volunteers aged 20 – 80 years were included in this study and divided into three age groups (A: 20 – 39y; B: 40 – 59y; C: 60 – 80y). All of the volunteers underwent magnetic resonance imaging (MRI) at 1.5 T with acquisition of sagittal T1ρ images. The calculated T1ρ relaxation times were correlated with age, BMI, gender, and lumbar level relative to the total disc, the annulus fibrosus, and the nucleus pulposus.Results Age had a significant influence on T1ρ relaxation times at all lumbar levels, with increasing age being associated with reduced relaxation times. There was also a significant difference between age groups A vs. C and B vs. C (P = 0.0008 and P = 0.0149, respectively). No significant differences in T1ρ relaxation time were observed between men and women (P > 0.05). BMI showed a significant negative correlation with T1ρ relaxation times (P < 0.0001). Analysis of the lumbar level revealed a significant decrease in relaxation times from L1/2 to L5 / S1 (P = 0.0013).Conclusion Increasing age correlated significantly with advanced lumbar disc degeneration in asymptomatic individuals, particularly in those aged 60 or older. Increasing BMI correlated significantly with increasing degeneration. The lower discs showed more degeneration than the upper ones.Key Points Citation Format
Keywords: t1ρ; spine; magnetic resonance imaging; lumbar disc; asymptomatic adults